Technical drawing - Goetsch, David L. (Delmar Publishers, 2000)
This text will prepare students for a career in drafting. This comprehensive, well-rounded text focuses on the graphic aspects of engineering and industrial technology. Material is updated to 1994 ANSI Standards. Chapter 1 is an introduction to CAD, and the last two chapters focus on how to obtain a job and how to function in a team environment